Board Interlock dan Kinerja Perusahaan dengan Board Diversity Sebagai Variabel Moderasi - Wisudanto Wisudanto; Suhartin Mohamad Syarif; Arif Kathon Subhekti (JURNAL ILMIAH EDUNOMIKA, 2024)
The researcher conducted this study to measure the effect of board interlock on company performance and moderated by the company’s board diversity. This study uses a population of non cyclicals consumer group companies on the main board on the Indonesia Stock Exchange for 2015 – 2020 period. The sample in this study were 29 companies and 174 observations. In this study, to measue the board interlock by counting number of positions on the company’s board, yo measure the company’s board diversity by using return on assets, while to measure the company’s board diversity by using the Blau index formula and coefficient of variance. Based on the results of the regression with SPSS 21, the board interlock has a significant positive effect on company performance. Meanwhile, board diversity plays a role in strengthening the positive influence of board interlock on company performance.